Advances in machining & manufacturing technology IX : selected papers from the 9th Conference on Machining & Advanced Manufacturing Technology in China, August 16-19, 2007, Harbin, China - Yao, Yingxue; Xu, Xipeng; Zuo, Dunwen (Trans Tech Publications, 2008)
This collection comprises 144 papers which were carefully selected from the over 300 papers submitted for the purposes of this special volume. All of the papers were subjected to peer-review by at least two expert referees. The papers were selected on the basis of their quality and their relevance to the topic. The resultant volume presents readers with the most recent advances in the field of machining and advanced manufacturing technology. It will therefore be invaluable to production and research engineers, research students and academics working in the field.
Keywords: Machining -- Congresses.; Manufacturing processes -- Congresses.; elektronické knihy; electronic books